Evaluation of a pheromone lure for capturing the agave weevil (Coleoptera: Curculionidae) - Rodríguez-Rebollar, Hilda; Rojas, Julio C.; González-Hernández, Héctor; Ortega-Arenas, Laura Delia; Equihua-Martínez, Armando; Del Real-Laborde, José Ignacio; López-Collado, José (Instituto de Ecología, A.C., 2012)
The agave weevil, Scyphophorus acupunctatus Gyllenhal, is considered the most important insect pest of the cultivated agaves in Mexico. Recent studies on the chemical ecology of this weevil have shown that males release a pheromone that attracts both sexes; the pheromone is composed of four components. Previous field experiments showed that all components, singled or in blends, were attractive to the weevils, but compounds 2-methyl-4-heptanone (C1) and 2-methyl-4-octanone (C2) were sufficient to obtain captures equivalent to those by the quaternary blend. In this study, we investigated the effect of different ratios (1:1, 1:2, 1:4, 2:1, and 4:1) and doses (50, 100, 150, 200, 350, and 500 mg)of C1 and C2 in the captures of the agave weevils in commercial plantations of Agave tequilana Weber. Our results showed that traps baited with synthetic pheromone captured more weevils than traps baited with adult male weevils but the different ratios of C1 and C2 did not affect the weevils capture. In fact, traps baited with C2 caught more weevils than those baited with the binary blend. Also, we found that weevil’s capture was not affected by dose. In general, traps baited with the synthetic pheromonal components caught more females than males.